Interleukin 13 (IL-13)-regulated expression of the chondroprotective metalloproteinase ADAM15 is reduced in aging cartilage - Yang, CY; Chanalaris, A; Bonelli, S; McClurg, O; Hiles, GL; Cates, AL; Zarebska, JM; Vincent, TL; Day, ML; Müller, SA; Lichtenthaler, SF; Nagase, H; et al. (Elsevier, 2020)
Objective The adamalysin metalloproteinase 15 (ADAM15) has been shown to protect against development of osteoarthritis in mice. Here, we have investigated factors that control ADAM15 levels in cartilage. Design Secretomes from wild-type and Adam15−/− chondrocytes were compared by label-free quantitative mass spectrometry. mRNA was isolated from murine knee joints, either with or without surgical induction of osteoarthritis on male C57BL/6 mice, and the expression of Adam15 and other related genes quantified by RT-qPCR. ADAM15 in human normal and osteoarthritic cartilage was investigated similarly and by fluorescent immunohistochemistry. Cultured HTB94 chondrosarcoma cells were treated with various anabolic and catabolic stimuli, and ADAM15 mRNA and protein levels evaluated. Results There were no significant differences in the secretomes of chondrocytes from WT and Adam15−/− cartilage. Expression of ADAM15 was not altered in either human or murine osteoarthritic cartilage relative to disease-free controls. However, expression of ADAM15 was markedly reduced upon aging in both species, to the extent that expression in joints of 18-month-old mice was 45-fold lower than in that 4.5-month-old animals. IL-13 increased expression of ADAM15 in HTB94 ​cells by 2.5-fold, while modulators of senescence and autophagy pathways had no effect. Expression of Il13 in the joint was reduced with aging, suggesting this cytokine may control ADAM15 levels in the joint. Conclusion Expression of the chondroprotective metalloproteinase ADAM15 is reduced in aging human and murine joints, possibly due to a concomitant reduction in IL-13 expression. We thus propose IL-13 as a novel factor contributing to increased osteoarthritis risk upon aging.